ANALISIS PEMETAAN STATUS PENGEMBANGAN EKONOMI LOKAL (PEL) DI KABUPATEN SUKOHARJO - ADI, R. KUNTO (Universitas Sebelas Maret, 2012)
Local Economic Development (LED) revitalization objective to change view ofstockholders included of Central Government, Regional Government, Non Government Institution, and community, for Local Economic Development (LED) to be instrument of developing economic activity was based on locally resources for increasing the sustainable of local community welfare.